2013
DOI: 10.1038/srep02878
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Solid/Nanoporous Copper/Oxide Hybrid Bulk Electrodes for High-performance Lithium-Ion Batteries

Abstract: Nanoarchitectured electroactive materials can boost rates of Li insertion/extraction, showing genuine potential to increase power output of Li-ion batteries. However, electrodes assembled with low-dimensional nanostructured transition metal oxides by conventional approach suffer from dramatic reductions in energy capacities owing to sluggish ion and electron transport kinetics. Here we report that flexible bulk electrodes, made of three-dimensional bicontinuous nanoporous Cu/MnO2 hybrid and seamlessly integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 61 publications
(164 reference statements)
1
32
0
Order By: Relevance
“…Obviously, TiO 2 nanotube arrays via anodization were amorphous, as reported elsewhere [24]. After electrodeposition, Cumodified TiO 2 nanotube arrays exhibited a new diffraction peak at 2θ = 43°, which can be assigned to crystal plane (111) of metal Cu [15,25]. Clearly, XRD results can effectively confirm the presence of metal Cu on amorphous TiO 2 nanotube arrays.…”
Section: Electrochemical Measurementssupporting
confidence: 67%
See 1 more Smart Citation
“…Obviously, TiO 2 nanotube arrays via anodization were amorphous, as reported elsewhere [24]. After electrodeposition, Cumodified TiO 2 nanotube arrays exhibited a new diffraction peak at 2θ = 43°, which can be assigned to crystal plane (111) of metal Cu [15,25]. Clearly, XRD results can effectively confirm the presence of metal Cu on amorphous TiO 2 nanotube arrays.…”
Section: Electrochemical Measurementssupporting
confidence: 67%
“…Besides the common anodic current collector, other applications of Cu additive material in various forms have also been reported in literatures [15,16]. For example, Cu was incorporated into the lattice of Mn 2 O 3 anode material to modulate the crystal structure, morphology, surface area, and Li-storage activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical capacity of 670 mAh g À1 is calculated based on the faradic reaction (diffusion controlled reactions) between Li and MoS 2 where 4 moles of Li reacts with MoS 2 to form Li 2 S and Mo. In practice, the obtained capacity from a lithium ion battery system not only comes from the faradic reactions but also from non faradic (capacitive reactions such as double layer capacitance and pseudocapacitance) [58][59][60] and side reactions (electrolyte decomposition and Li + adsorption on SEI layers) [61]. Several researchers observed that the capacity contribution from capacitive reaction could be up to 30 to 60% of the total capacity [60].…”
Section: Resultsmentioning
confidence: 99%
“…88 On the other hand, the oxidation peak at ;2.2 V in the anodic sweep exhibits little change during the three cycles, suggesting that the SEI formed on the PGC nanosheets surfaces in the first cycle is very stable.…”
Section: Ultrafine Tmo Nanoparticles Encapsulated By Carbonous Mamentioning
confidence: 95%